If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(2t + -5) = 3 Reorder the terms: -3(-5 + 2t) = 3 (-5 * -3 + 2t * -3) = 3 (15 + -6t) = 3 Solving 15 + -6t = 3 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -6t = 3 + -15 Combine like terms: 15 + -15 = 0 0 + -6t = 3 + -15 -6t = 3 + -15 Combine like terms: 3 + -15 = -12 -6t = -12 Divide each side by '-6'. t = 2 Simplifying t = 2
| 1.5+x=7.5 | | 3(x-4)=63 | | sqrt(n)*(4+6n)= | | -55=3x+6x+8 | | 6.7x-3.8=16.3 | | 5(3z-1)-3(z+7)=7(z+1) | | 20s=-140 | | 17-13d=-11d-19 | | 6b-(2b+8)=-16 | | 6x-11=2(5x-30)+9 | | 3+4(x-8)=9-8(8-5) | | 21+28m=28+21m | | x+11=2x-4 | | q+12=-2 | | x^3y^2-x^4y+4xy^3=0 | | 2x+3=59 | | 5=5x-6x-5 | | -2(4t-3)=6 | | 5x+4(-2-3)=-10-5x | | 2x^2+13x-21=1 | | 2x^2-y^2=1200 | | -2x+6(3x-7)=-22-4x | | 6x-3=-23+x | | 6m+5n+9m+7n= | | 2w^2+3=90 | | n+(n+1)+(n+2)=111 | | 10c-5(20-c)= | | d-4n=-2 | | 3x^2-6x=5x^2-7x | | 2x^2-53x+120=0 | | 8(2n+2)=8(9n+1)+3 | | 5-7x=-58 |